The Need for Affiliation and Assertive Behavior in Students Joining Student Organizations: Kebutuhan Afiliasi dan Perilaku Asertif pada Mahasiswa yang Mengikuti Organisasi Kemahasiswaan - Istgahfirul, Qolbi; Maryam, Effy Wardati (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the relationship between the need for affiliation with assertive behavior in students who follow student organizations at the University of Muhammadiyah Sidoarjo. The research uses a correlational quantitative approach. The sampling technique in this study is a proportional non random sampling technique with a sample size of 301. Data collection uses a psychological scale with a Likert scale model, namely affiliation needs scale and assertive behavior scale. Data analysis using Pearson Product Moment correlation technique using SPSS 25.0 for windows program. The results of this study indicate rxy = 0.606 and with a significance value of 0.000 where p <0.05, which means the researcher's hypothesis is accepted, namely there is a positive and significant relationship between the need for affiliation and assertive behavior in students who follow student organizations at the University of Muhammadiyah Sidoarjo. The effect of affiliation needs on assertive behavior is 36.7%.